Evaluation of the level of soil degradation in two productive systems in the Quibor depression. I. Multivariate analysis (Bioagro, 2020)
In the horticultural zone of Quíbor, Lara State, Venezuela, cultivation of furrow irrigated onion has been applied as a conventional management system, although changes are currently being implemented in horticultural production, such as the move towards the conventional system of cultivation of super sweet corn, which could affect the soil. The objective of this work was to evaluate, using multivariate analysis, the level of degradation that might exist in the soil of the two productive systems. A large-plot experiment was applied by sampling in a 10 x 10 grid in the soils of both production systems. At each sampling point, soil samples were taken in three strata (0-5, 5-18 and 18-50 cm deep) and we measured the following attributes: chemical (pH, EC, macronutrient content, CEC and total nitrogen); physical (texture, particle size distribution, apparent density, total porosity, macro and micro-porosity, saturated hydraulic conductivity and aggregate stability), and biological (basal respiration, microbial biomass, metabolic coefficient and the microbial carbon-organic carbon ratio). The principal component analysis allowed to define the chemical, physical, chemical and biological attributes that best reflected the degradation conditions in each soil. Important degradation conditions were found in both soils, which are related to the intrinsic and management characteristics of each productive system.
Keywords: Fertigation; onion; soil management; super sweet corn